Teacher Strategies in Administering Remedial Exams to Improve Learning Achievement of Arithmetic Operations Material in Elementary Schools - Prasetyaningrum, Ratna Budi; Hasanah, Enung; Zuhaery, Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze teacher strategies in administering remedial exams to improve the learning achievement of arithmetic operations in elementary schools. The study used a qualitative case study design with a qualitative approach conducted at Muhammadiyah Condongcatur Elementary School, Sleman Regency, Yogyakarta Special Region. The research subjects consisted of one fourth-grade teacher and two fourth-grade students who experienced difficulties in learning mathematics. Data were collected through in-depth interviews and documentation, then analyzed interactively through the stages of data collection, data reduction, data presentation, and conclusion. The results showed that teacher strategies in administering remedial exams include four main aspects, namely planning, implementation, monitoring or supervision, and remedial strategies. In the planning aspect, teachers make special schedules, give preliminary assignments, adjust the form of questions, and communicate intensively with students and parents. In the implementation aspect, remedial exams are carried out in a controlled manner with an emphasis on honesty, independence, and teacher guidance. The monitoring aspect is carried out through gradual corrections and re-discussions to diagnose student misconceptions. Remedial strategies are applied flexibly, adaptively, and repeatedly until learning completeness is achieved according to the principles of mastery learning. The main obstacle identified was students' low mastery of the prerequisite material. This study concluded that pedagogically and diagnostically managed remedial exams can significantly improve learning outcomes, not just improve academic grades.